Experiences of doctoral students enrolled in a research fellowship program to support doctoral training in Africa (2014 to 2018): The Consortium for Advanced Research Training in Africa odyssey (2021)
Background The Consortium for Advanced Research Training in Africa (CARTA) aims to transform higher education in Africa. One of its main thrusts is supporting promising university faculty (fellows) to obtain high quality doctoral training. CARTA offers fellows robust support which includes funding of their attendance at Joint Advanced Seminars (JASes) throughout the doctoral training period. An evaluation is critical in improving program outcomes. In this study; we, CARTA fellows who attended the fourth JAS in 2018, appraised the CARTA program from our perspective, specifically focusing on the organization of the program and its influence on the fellows’ individual and institutional development. Methods Exploratory Qualitative Study Design was used and data was obtained from three focus group discussions among the fellows in March 2018. The data were analyzed using thematic approach within the framework of good practice elements in doctoral training–Formal Research Training, Activities Driven by Doctoral Candidates, Career Development as well as Concepts and Structures. Result In all, 21 fellows from six African countries participated and all had been in the CARTA program for at least three years. The fellowship has increased fellows research skills and expanded our research capacities. This tremendously improved the quality of our doctoral research and it was also evident in our research outputs, including the number of peer-reviewed publications. The CARTA experience inculcated a multidisciplinary approach to our research and enabled significant improvement in our organizational, teaching, and leadership skills. All these were achieved through the well-organized structures of CARTA and these have transformed us to change agents who are already taking on research and administrative responsibilities in our various home institutions. Unfortunately, during the long break between the second and the third JAS, there was a gap in communication between CARTA and her fellows, which resulted in some transient loss of focus by a few fellows. Conclusion The CARTA model which builds the research capacity of doctoral fellows through robust support, including intermittent strategic Joint Advanced Seminars has had effective and transformative impacts on our doctoral odyssey. However, there is a need to maintain the momentum through continuous communication between CARTA and the fellows all through this journey.